BẢO TỒN TRONG BỐI CẢNH XÃ HỘI: ĐÁNH ĐỔI GIỮA BẢO TỒN VÀ PHÁT TRIỂN - Thắng, Hoàng Văn (Nhà xuất bản Nông nghiệp, 2016)
The Advancing Conservation in a Social Context: Working in a World of Trade-offs Initiative (ACSC) was designed to promote productive and meaningful research and discussion about the relationship between biodiversity conservation, social well-being, and economic development in Viet Nam. Given Vietnam’s unique history and socio-political context, a primary emphasis of the research initiative undertaken by the Centre for Natural Resources and Environmental Studies (CRES) was to examine and digest the volume of relevant technical reports, laws and policies, and other documents in such a way that they can be used to understand and intervene in the trajectory of conservation and development in Vietnam. From this analysis, we were able to summarize and categorize Vietnam’s history with respect to the social and decision making context of conservation and development decisions through three different time periods, and create a typology of the multiple kinds of relationships between conservation and development activities that occur in Vietnam. Vietnam has experienced a significant process of change and development in its management of natural resources, its socio-economic situation, its social organization, and its institutions and policies since 1960. These changes are a result of a series of important historical events as well as the political economy and related policies of the country. Before 1986, trade-offs between development and conservation were not described in strategies and policies of the government and the communist party. Since 1986, trade-offs have been taken into consideration in the communist party and the government’s strategy and policies.